Al Qasimi Foundation 2013
DOI: 10.18502/aqf.0110
|View full text |Cite
|
Sign up to set email alerts
|

Home Environment, Family Involvement, and Emirati College Student Academic Achievement

Abstract: In educational literature set in Western contexts, student performance is linked to positive family involvement and home environment; however, literature on the educational experience of college students in non-Western contexts, including the Gulf region, is scarce. Using both student and guardian surveys, this quantitative study investigates the effect of home environment and family involvement on the educational experience of students in a federally funded college in the United Arab Emirates (UAE) as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Families in the UAE are generally supportive of education but lack academic support systems (Daleure et al, 2013). Older generations with limited education may also struggle to support students underachieving or struggling academically.…”
Section: Attitude Towards Educationmentioning
confidence: 99%
“…Families in the UAE are generally supportive of education but lack academic support systems (Daleure et al, 2013). Older generations with limited education may also struggle to support students underachieving or struggling academically.…”
Section: Attitude Towards Educationmentioning
confidence: 99%
“…Recent studies have compared the lives of UAE nationals in four different generational categories according to experience level and age (Daleure, Albon & Hinkston, 2014;Daleure, Albon, Hinkston, Ajaif, & McKeown, 2013). The studies found that elder generations' influence on younger family members' crucial life decisions, such as deciding to continue with post-secondary education, program choices, and career moves, may be well-meaning but misguiding.…”
Section: Social Transitions Resulting From Developmentmentioning
confidence: 99%
“…First of all, the figures most frequently quoted are prior to the wage dip caused by the financial crisis in 2008 and the highest estimates (i.e., AED 40,000 or USD 10,899 or more) are quoted for Abu Dhabi, where the highest overall salaries are found. The most important factor, however, is one previously mentioned by Daleure et al (2013) which is the nature of Emirati family structure, in which all male-and, increasingly, female-members of the family contribute to the overall family income. If two spouses are working, with each spouse earning the average salary in the study of AED 15,000, then the total household income would be AED 30,000.…”
Section: Fire: Forum For International Research In Educationmentioning
confidence: 99%
“…Recent studies (Daleure et al, 2013(Daleure et al, , 2014 have compared the lives of UAE nationals in four different generational categories according to stages of development each has experienced: youth cohort-not yet graduated high school (less than 16 years old), young adult cohort-college-aged generation (from 16 to 25 years old), mature adult cohort-completed college, likely working, likely married and raising a family (from 35 to 55 years old) and grandparents' generationmemories of life before nationalisation (older than 55 years old). Table A1 lists the categories and specific attributes of each.…”
Section: Challengesmentioning
confidence: 99%
“…The current study (referred to here as Ethnography Study ) examines the experience, attitudes and beliefs of the elder generation—those with recollection of life before nationalisation in 1971—to understand the basis of the modern Emirati identity, cultural practices and sensitivities. Recent studies including AlAli (2013), Daleure, Albon, and Hinkston (2014), and Daleure, Albon, Hinkston, Ajaif, and McKeown (2013) found that as a society with tribal roots, elders have an enormous influence on important educational, career and employment decisions of young adult members. However, the progressive generations lived during different phases of economic growth and experienced a different set of circumstances.…”
Section: Introductionmentioning
confidence: 99%